Humor interventions in psychotherapy and their effect on levels of depression and anxiety in adult clients, a systematic review - Sarink, Federico S. M.; García-Montes, José M. (Frontiers in Psychiatry, 2023)
Humor as a valuable construct in psychology has been the subject of much discussion for many years, and has received increased attention more recently in the field of positive psychology. However, empirical research on the application of humor in a clinical setting with depressed or anxious clients has been difficult to discover. Because of the potential benefits and the low costs of providing humorous interventions our goal was to give an overview of the studies conducted in psychotherapy and to show the effect of humor on the levels of depression and anxiety symptoms. Furthermore, we wanted to assess the empiric support of humor as a clinical intervention in psychotherapy according to the SIGN system. We used the PRISMA guidelines. Because of the differences in design of the ten included studies, it was not possible to perform a meta-analysis. Results from studies performed in seven different countries show that humorous interventions can have significant positive effects on symptoms of depression and anxiety. The results also confirm the prior observation that empirical research in the field is based on different designs with different populations and different methods of translating the abstract concept of humor in measurable observations. The results need to be considered with caution because of the methodological limitations of the research to date. Some authors advocate for an integrative approach to continue research on humor in psychotherapy. It is our recommendation to first focus on the separate aspects of humor and to conduct research based on sound methodology. To initiate wider research to the application of humor in psychotherapy we propose an approach to humorous interventions based on surprise and confusion which can help clients to search for an alternative framework to resolve the confusion and therefore promote taking on new perspectives and distancing themselves from the actual problem.